CORRELATION AND IMPLEMENTATION OF PHILOSOPHY OF PANCASILA IN INDONESIAN CRIMINAL SYSTEM - Vincentius patria; Itok Dwi Kurniawan (Prodi PPkn Universitas Slamet Riyadi, 2022)
The criminal system in Indonesia is still shackled to the influence of the criminal system inherited by the Dutch, which breathes liberalism. This is reflected in the criminal laws in Indonesia which still refer to the colonial legacy law. The criminal system that exists to this day is not based on the local wisdom of the Indonesian people, so it does not reflect Pancasila which is a value that is firmly held by the Indonesian people and is the source of all sources of law. The purpose of this paper is to examine the concept of punishment which shows the correlation and implementation of the Pancasila philosophy in the criminal system in Indonesia. The method used in this paper is a normative legal research method, with a conceptual approach and legislation. The result of this research is the relationship between the criminal system and the implementation of Pancasila values. Keywords: Criminal System, Pancasila, Philosophy.